Pole Test and Ankle-Brachial Index by Using Doppler Ultrasound for Peripheral Arterial Disease in End-Stage Renal Disease Patients - Nutthanun Tungsrirut (2020)
© The Author(s) 2020. Peripheral arterial disease (PAD) causes great disability in end-stage renal disease (ESRD). Pole test is a simplified test utilizing the basis of Doppler ultrasound invented to correct false elevation in ankle-brachial index (ABI) in diabetic patients with severe calcification of the tibial artery. However, the role of pole test in ESRD patients is still unclear. The aim of this study was to explore the sensitivity, specificity, and overall utility of pole tests in such patients. One hundred and four patients were recruited and examined with 3 tests: pole test, ABI, and toe-brachial index, the latter serving as the gold standard. Receiver operating characteristic analysis was performed using SPSS version 22.0. The sensitivity, specificity, and other diagnostic values of ABI and pole tests were calculated. There were 104 ESRD patients enrolled. Pole tests showed to have low probability to provide accurate results (area under the curve = 0.505, standard error = 0.042). Low sensitivity of ABI (34.96%) can be observed in ESRD patients. Specificity, positive predictive value, and negative predictive value of ABI in all cases were, respectively, 85.91%, 81.13%, and 43.26%. It is concluded that pole test accuracy seemed to be limited in ESRD patients. ABI was found to be confounded by medial arterial calcification, resulting in low sensitivity as well. The results of this study permit the observation that an optimal tool for screening peripheral arterial disease in ESRD patients remains to be discovered.